Observational study of temporomandibular joint pain in osteoarthritis patients - Sahul Hameed Abdul Samad; Mohan Narayanan; Thiruneer Vannan; Swapna Killamsetty; Jagadeesh Konchada; Kopparesh Deshpande (Journal of Indian Academy of Oral Medicine and Radiology, 2015)
Aim: The aim of this study was to evaluate the incidence of temporomandibular joint (TMJ) pain in osteoarthritis patients. Objectives: The three objectives of this study were as follows: 1. finding the occurrence of TMJ pain in osteoarthritic patients; 2. to evaluate the signs of TMJ disorders in osteoarthritic patients; and 3. to assess the involvement of TMJ in osteoarthritic patients. Materials and Methods: Twenty osteoarthritis patients who were under treatment for a minimum of 1 year were included in this study. All of them answered a questionnaire before undergoing examination. The questions pertained to the symptoms of the TMJ pain. Clinical examination of TMJ was done, which included evidence of sound, restricted mouth opening, and deviation. Results: Results indicated that about 40% of osteoarthritis patients had TMJ pain. Conclusion: This study shows the high incidence of TMJ pain in patients with osteoarthritis.